Berberine Suppresses TNF-Î±-induced MMP-9 and Cell Invasion through Inhibition of AP-1 Activity in MDA-MB-231 Human Breast Cancer Cells - Jae Hyuck Choi (Molecules, 2008)
Invasion of cancer cell induced by matrix metalloproteinase-9 (MMP-9) is one of pivotal steps in cancer metastasis. Herein, we investigated how cell invasion was regulated by berberine (BBR), an isoquinoline derivative alkaloid compound, in MDA-MB-231 human breast cancer cells. The basal level of MMP-9 activity and expression was dose-dependently increased by TNF-Î±, while TNF-a-induced MMP-9 gelatinase activity and expression was decreased by BBR. To investigate regulatory mechanism of TNF-Î±-induced MMP-9 expression, we pretreated cells with UO126 (MEK inhibitor), SB203580 (p38 inhibitor) and SP600125 (JNK inhibitor), respectively. Interestingly, TNF-Î±-induced MMP-9 activity and expression was decreased by UO126 and SB203580, but not by SP600125. Therefore, we further examined the effects of BBR on TNF-Î±-induced AP-1 DNA binding activity which is a downstream target of ERK and p38. Our data showed that TNF-Î±-induced AP-1 DNA binding activity was inhibited by BBR. Finally, we investigated the effect of BBR on TNF-Î±-induced cell invasion. TNF-Î±-induced cell invasion was significantly decreased by BBR treatment. Taken together, we suggest that TNF-Î±-induced MMP-9 expression and cell invasion are decreased by BBR through the suppression of AP-1 DNA binding activity in MDA-MB-231 human breast cancer cells.